Enhancement of nonwoven cellulose triacetate forward-osmosis membranes by surface coating modification - Aly, Hanaa; Gadallah, Hanaa; Ali, Sahar; Sabry, Rania (International Journal of Engineering and Technology, 2017)
Forward osmosis (FO) is considered as one of the emerging techniques in membrane technology. The enhancement of FO performance is governed by two major factors: the first one is development of high-performance draw solutions and the second is utilizing of high efficient FO membranes. The aim of this work is to investigate chemical surface coating modification of commercial nonwoven forward osmosis membrane with new hydrophilic coating materials namely, o-phenylene di-amine and benzoyl chloride. The effect of coating addition at different concentrations was studied. The membrane morphology and chemical structure characterization of modified membranes proved the formation of dense layer and higher membrane porosity. Finally, it was demonstrated that increasing of coating material concentration gradually increases porosity and membrane performance till 0.75 g/l. By further increasing of coating materials, the porosity and membrane performance tend to decrease.